Impact of Dietary Vitamin E and Selenium on Production Performance in Japanese Quail - Mohammed Adulkareem Wahab; Mahmood Hasan Mohammed Ameen; Dilshad Namiq Khwrshed (مجلة الانبار للعلوم البيطرية, 2024)
The purpose of the current study was to study the impact of dietary supplementation of various levels of vitamin E and inorganic selenium (Sodium selenite) on daily egg weight, egg mass and egg production, accumulative egg per hen per week, final body weight gain for males, and feed conversion in both males and females of Japanese quail birds (Coturnix coturnix japonica). The study was conducted in the nutritional laboratory at the Veterinary Techniques Department/ Kalar Technical Institute /Garmian Polytechnic University in the Iraqi Kurdistan region for eight weeks from Apr 15 2021 to Jul 15 2021. In this study 128 birds (12 weeks old) were employed, they were raised in a cage system, measuring 50 width inches x 60 lengths inches × 60 height inches. Four supplemented dietary treatments from the experimental birds were designed as different levels of food regimens, and then each treatment was subdivided equally into eight replicated cages. The used experimental diets were: 0 = the basal diet (control) with no additions, T1 = 1.0-gram vitamin E and selenium mixture/kg diet, T2 = 1.5-gram vitamin E and selenium mixture/kg diet, T3 = 2-gram vitamin E and Selenium mixture/kg diet. As a result of this study, egg production (HD%/week), egg accumulation (eggs per hen per week), egg mass (gram per day), feed intake (gram per day), and feed conversion ratio (kilogram feed per kilogram egg) were altered significantly (P0.01). In conclusion, it was shown that vitamin E and sodium selenite were effective supplementary nutrients for enhancing the reproductive performance of Japanese quail hens, so it is recommended to use this diet in different poultry farms in order to increase some productive and reproductive features levels. [AJVS 2024; 17(2.000): 95-104]